Muon Imaging of Volcanic Conduit Explains Link Between Eruption Frequency and Ground Deformation. Issue 2 (13th January 2023) - Oláh, László; Gallo, Giuseppe; Hamar, Gergő; Kamoshida, Osamu; Leone, Giovanni; Llewellin, Edward W.; Lo Presti, Domenico; Nyitrai, Gábor; Ohminato, Takao; Ohno, Shouhei; Tanaka, Hiroyuki K. M.; Varga, Dezső
Abstract: Understanding the physical mechanism of ground deformation at a volcano supports the use of deformation data as a monitoring tool. An inverse correlation was observed between eruption frequency and ground deformation of Sakurajima volcano from November 2018 to April 2021. Over the same period, the mass density of magma in the conduit was monitored via muography. Mass density increased during inflation, when eruption frequency was low, and decreased during deflation, when eruption frequency was high. Periods of low eruption frequency are associated with the formation of a dense plug in the conduit, which we infer caused the inflation of the edifice by trapping pressurized magmatic gas. Conversely, periods of high eruption frequency are associated with the absence of the plug, which we infer allows gas to escape, leading to deflation. Muography thus reveals the in‐conduit physical mechanism for the observed correlation, with implications for interpretation of deformation at other volcanoes. Plain Language Summary: The ground surface of a volcano often deforms before an eruption. Remote sensing of ground movements could be a valuable tool for eruption forecasting if the physical causes of ground deformation were known. We have used naturally occurring cosmic muons to image the changes in mass density over time in the upper plumbing system of Sakurajima Volcano (Japan) and compared this with ground surface motions and eruption activity. We found that the mass density increased during dormant periods, when the ground surface of the volcano was high, and the mass density decreased during periods of frequent eruption, when the ground surface was low. Muon imaging helped to reveal the hidden volcanic processes: the volcano plugged with dense magma during dormant periods allowing pressure in the conduit to build up, resulting in the uplift of the volcano's surface. During periods of eruption, the plug was destroyed and replaced with fresh, lower‐density magma, releasing pressure and causing the volcano's surface to move downwards. Key Points: An inverse correlation was observed between eruption frequency and ground surface deformation of Sakurajima volcano Beneath the crater, muon imaging visualized that the mass density increased during ground inflation and decreased during ground deflation Plugging of the conduit with dense, stiff magma during recharge caused inflation during quiescent periods